A new shrubby species of Nasa Weigend ser. Carunculatae (Urb. & Gilg) Weigend (Loasaceae) from the Amotape-Huancabamba Zone - Henning, Tilo (2009)
Nasa is the largest genera in the Loasaceae family and it is particularly speciose in the Amotape-Huancabamba Zone of northern Peru. Nasa ser. Carunculatae is a group of four species, three of them endemic to the Amotape- Huancabamba Zone. Species in this group are characterized by their shrubby habit, deciduous leaves, and typical tilt-revolving flowers with white to greenish petals. In this work, we describe a new species of Nasa ser. Carunculatae from the southern limit of Amotape-Huancabamba area, La Libertad, Peru. The species differs from others in having much smaller and notably narrower leaves. Unlike all the other species of ser. Carunculatae, the entire distal portion of the stem is densely glandular. It is apparently most closely related to Nasa carunculata, a species known from inter-Andean valleys of Ancash and Ayacucho.